Contamination and Health Risk Assessment of Exposure to Heavy Metals in Soils from Informal E-Waste Recycling Site in Ghana - Kyere, Vincent N.; Greve, Klaus; Atiemo, Sampson M.; Amoako, Doris; Aboh, IJ Kwame; Cheabu, Benjamin S. (Ital Publication, 2018)
The objective of this study is first, to investigate the level of heavy metals in soils from Agbogbloshie e-waste processing site (AEPS), the degree at which these heavy metals contaminate the area and finally, to assess the carcinogenic and non-carcinogenic health risk of heavy metals on workers and residents in around the AEPS. 132 soil samples were collected from the study area and the samples analyzed for Ba, Cd, Co, Cr, Cu, Hg, Ni, Pb and Zn heavy metals after appropriate preparations were made. Results of the analysis showed mean concentrations of Cd, Cr and Ni considered as carcinogenic were lower than permissible levels of Dutch and Canadian soil standards. Mean concentrations however of Cu, Pb and Zn were between 100% and 500% higher than the permissible levels. Assessment of the degree of Contamination indicated Ni<Ba<Co<Cr<Zn<Hg<Cu<Cd<Pb in an increasing order as contributing to the degree of contamination with according to the degree of contamination index the burning, dismantling, residential and commercial considered as very highly contaminated. The health risk analysis of individual heavy metals in soil indicated non-carcinogenic risk of Cr, Hg and Pb with hazard index above the safe level of 1 in the burning and dismantling areas and as such could trigger neurological and developmental disorders in children less than six (6) years.